1984
DOI: 10.1021/bi00315a004
|View full text |Cite
|
Sign up to set email alerts
|

Reduction kinetics of purified rat liver cytochrome P-450. Evidence for a sequential reaction mechanism dependent on the hemoprotein spin state

Abstract: The anaerobic reduction kinetics of purified rat liver ferric cytochrome P-450 from phenobarbital-treated rat liver microsomes, reconstituted with saturating NADPH-cytochrome P-450 reductase, have been investigated and were shown not to be monophasic. From experiments correlating changes in the rate of fast-phase reduction with the spin state of the heme iron existing at preequilibrium, data were obtained consistent with a model for spin-state control of cytochrome P-450 reduction wherein the high-spin form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Furthermore, a conversion from the hexa-coordinated low-spin to the penta-coordinated high-spin state, which is triggered by reduction of the reductase flavins may have an important impact on the catalytic efficiency and coupling of the P450. This transition is known to increase the rate of the electron transfer [2, 4, 5, 7] due to a considerable decrease in the reorganization energy associated with the reduction process [67, 68] along with a positive displacement of the redox potential of cytochromes P450 [69, 70], and 3A4 [71] in particular. At the same time, the modulation of the spin state of cytochromes P450 in response to the changes in the redox state of the reductase may explain an apparent lack of correlation between the rate of NADPH-dependent reduction or the rate of substrate turnover and the spin-state for certain microsomal cytochromes P450 [8], which was considered as a disproof of the theory of the spin-state control of the rate of electron transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a conversion from the hexa-coordinated low-spin to the penta-coordinated high-spin state, which is triggered by reduction of the reductase flavins may have an important impact on the catalytic efficiency and coupling of the P450. This transition is known to increase the rate of the electron transfer [2, 4, 5, 7] due to a considerable decrease in the reorganization energy associated with the reduction process [67, 68] along with a positive displacement of the redox potential of cytochromes P450 [69, 70], and 3A4 [71] in particular. At the same time, the modulation of the spin state of cytochromes P450 in response to the changes in the redox state of the reductase may explain an apparent lack of correlation between the rate of NADPH-dependent reduction or the rate of substrate turnover and the spin-state for certain microsomal cytochromes P450 [8], which was considered as a disproof of the theory of the spin-state control of the rate of electron transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no commonly accepted hypothesis on the mechanism of this biphasicity, its close connection to the position of P450 spin equilibrium is beyond doubt. In most cases, displacement of the spin equilibrium towards the high spin state caused by addition of Type I substrates increases the fraction of the fast phase [2, 4, 5, 7]. Furthermore, in some cases, the first exponential phase of reduction was shown to represent solely the reduction of the high-spin heme protein [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Those results reveal a strict correlation between the rate of substrate N -demethylation and its coupling to NADPH oxidation with the amplitude of the substrate-induced spin shift. Furthermore, the low-to-high spin transition is known to increase the rate of electron transfer to cytochromes P450 (Tamburini et al , 1984; Backes et al , 1985; Backes and Eyer, 1989) due to a considerable decrease in the reorganization energy associated with the reduction process (Honeychurch et al ., 1999; Denisov et al ., 2005) along with a positive displacement of the P450 redox potential (Fisher and Sligar, 1985). This has been demonstrated with CYP3A4 (Das et al , 2007) in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies suggested that the heme iron spin state may serve as a surrogate marker (Sligar et al, 1979;Tamburini et al, 1984;Backes et al, 1985). Although not applicable for every P450 isoform (Eyer and Backes, 1992) as a result of differences in reduction potentials (Ost et al, 2003), CYP2C9 is reduced much faster in the presence of substrate even though the substrate oxidation rate may be slow (Guengerich and Johnson, 1997).…”
Section: Discussionmentioning
confidence: 99%